2021
DOI: 10.1037/pspp0000379
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and satisfaction with social relationships across time.

Abstract: Research on the longitudinal association between self-esteem and satisfaction with social relationships has led to ambiguous conclusions regarding the temporal order and strength of this relation. Existing studies have examined this association across intervals ranging from days to years, leaving it unclear as to what extent differences in timing may explain differences across studies. In the present study, we used continuous time structural equation models (i.e., CT-SEM) to examine cross-lagged relations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 78 publications
(156 reference statements)
1
27
0
Order By: Relevance
“…The two nested models were compared with a likelihood ratio test (Δ−2LL) and by examining the change in Akaike’s information criteria (ΔAIC). Mean-level changes were interpreted as significant if ΔAIC > 4 and if the likelihood ratio test was significant (de Moor et al, 2021). Using this procedure, we could examine whether there were overall mean-level changes in the latent process with the passing of time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two nested models were compared with a likelihood ratio test (Δ−2LL) and by examining the change in Akaike’s information criteria (ΔAIC). Mean-level changes were interpreted as significant if ΔAIC > 4 and if the likelihood ratio test was significant (de Moor et al, 2021). Using this procedure, we could examine whether there were overall mean-level changes in the latent process with the passing of time.…”
Section: Methodsmentioning
confidence: 99%
“…Meanlevel changes were interpreted as significant if DAIC . 4 and if the likelihood ratio test was significant (de Moor et al, 2021). Using this procedure, we could examine whether there were overall mean-level changes in the latent process with the passing of time.…”
Section: Using Continuous Time Models To Answer the Research Question...mentioning
confidence: 99%
“…Empirical research has highlighted its predictive relevance for social, psychological, and health-related outcomes , prompting numerous studies to address the question of how self-esteem is formed. Over the past decades, it has been repeatedly demonstrated that selfesteem is shaped by social interactions and relationships with others (de Moor et al, 2021;Harris & Orth, 2019;Leary et al, 1995). While a great amount of research supports the link between the perception of feeling socially included and self-esteem, first studies show considerable differences in the degree to which momentary selfesteem fluctuates in response to these perceptions (Poorthuis et al, 2014;Schmidt et al, 2020;Thomaes et al, 2010).…”
mentioning
confidence: 99%
“…Like other longitudinal studies before it, Karakter was constrained by factors such as funding and personnel needs, and it is likely that this is one reason why the issue of timing regarding personality change (e.g., at what time interval should expect personality change to occur?) has been relatively neglected (e.g., de Moor et al, 2021;Luhmann et al, 2014). Ideally, we would have followed our participants for a longer period of time, as it would offer more information with regards to people's trajectories.…”
Section: Methodological Challengesmentioning
confidence: 99%